The City of Mosul and its Archaeological, Heritage and Cultural Monuments, From Occupation to Terrorism - Abdullah Khursheed Qader; Sherzad Musher Abdullah (QALAAI ZANIST JOURNAL, 2021)
All studies and research are in agreement regarding the destruction caused to Mosul by the occupation and terrorism that targeted the city in all its areas and aspects, including the archaeological, heritage, cultural and religious monuments, which are among the most basic elements of the national human and cultural civilization. Antiquities and heritage are the permanent balance of experiences, experiences and attitudes that give the human being and society the ability to face the present and the future. What happened to the city of Mosul is a planned and deliberate matter in emptying it of its cultural content, as it has been subjected to systematic robbery, destruction and smuggling operations that are the largest in history, especially when the terrorist organization (ISIS) invaded it in 2014 So he began to systematically destroy the Mosul Museum and archeological sites dating back to the second millennium BC, and plunder of small pieces and selling them on the black market. Iraq was and is still from north to south and in every city, district and sub-district, it has a great archaeological asset at the level of civilization that extends for tens of thousands of years, with the presence of more than two hundred thousand archaeological sites, only twelve thousand sites were known and excavated. The figures that talk about the cultural, archaeological, religious and cultural landmarks that ISIS targeted and destroyed in the city center of Mosul have not been identified to this day, although the reports have identified many of them and most of them, but these matters were not accurate and the reason is that we did not have a previous database that gives us precisely the size of the total and complete destruction of the city. Mosul. The issue of smuggling and theft of antiquities was not new. Its old case began at the beginning of the nineteenth century as a result of factors including the supremacy of the biblical culture, which coincided with some religious facts and scientific facts. The greatest and most beautiful monuments of Iraq by the campaigns carried out by the Westerners, with political fronts and an archaeological cover. The assessment of what happened in general in Iraq after 2003 and what the reports mentioned was that when the US invasion of Iraq more than fifteen thousand original artifacts were lost, ranging from ornate Abbasid art pieces to stone statues, as well as the theft of (five thousand) cylindrical seals and gold and silver ornaments from important Abbasid sites.